Protection of Women from Sexual Violence: Reconciling Gender Justice from an Islamic Perspective - Atikah Rahmi; Asmuni Asmuni; Nurasiah Nurasiah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Empirical facts show that the number of sexual violence in various forms is increasing, while victims still experience difficulties in obtaining protection which is the responsibility of the State. Sexual violence experienced by women is a manifestation of historical inequality in power relations between men and women and is a structural obstacle to achieving social justice, peace and sustainable self-development. The aim of this research is to analyze the protection of women from acts of sexual violence that fulfills the benefits and is gender equitable for women. Through a normative juridical method with a statutory approach and legal principles, research was conducted sourced from secondary data, reinforced by interviews coded via NVivo R1. The results of the research show that the strong patriarchal viewpoint in Indonesian society gives rise to gender inequality and is a contributing factor to sexual violence against women. Sadly, this action is still considered an immoral act by some people. Victims still experience revictimization due to society's mindset that does not side with women as victims and instead blames them for triggering sexual violence. For this reason, it is hoped that all elements of society will no longer be permissive regarding the issue of sexual violence, so that efforts are needed to make socio-cultural changes in Indonesia, one of which is through gender reconciliation by applying the principle of mubindah in life. So that sexual violence can be eliminated and victims can be protected.